Statin-induced rhabdomyolysis in a 60-year-old woman with decompensated type 2 diabetes: a case report - O. V. Tsygankova (Российский кардиологический журнал, 2021)
Rhabdomyolysis is a very rare and most severe form of statin-induced muscle adverse event characterized by muscle pain, muscle necrosis with myoglobinemia and/or myoglobinuria with a very high risk of acute kidney injury and death. The article presents a case report of developing rhabdomyolysis in a middleaged female patient with hypertension, decompensated type 2 diabetes and albuminuria. A 60-year-old woman was admitted to the hospital for emergency indications with complaints of severe muscle weakness that began in the neck, which spread over several days to the upper and lower extremities, with a symptoms progression up to paresis. According to the appointment of a primary care physician, three months before hospitalization, the patient was switched from therapy with European generic brand-name rosuvastatin 20 mg to the Russian generic unbranded atorvastatin in the same dose (20 mg), which is not comparable in lipid-lowering effect. In a laboratory study, an increase in creatine phosphokinase level by 348 times (50462 U/L) of upper normal limit in combination with severe hypokalemia 1б7 mmol/L in the absence of renal dysfunction was recorded. Cancellation of statin, metformin and empagliflozin, intensive infusion therapy and treating electrolyte imbalance made it possible to prevent the development of acute renal damage, life-threatening arrhythmias and completely stop muscle complaints within a few days. The patient was discharged from the hospital on the 23rd day with reference clinical and laboratory values, including creatine phosphokinase.This case emphasizes the importance of maintaining clinical suspicion regarding rhabdomyolysis in patients receiving statin therapy in the presence of risk factors (in this case, female sex, hyperglycemia, chronic kidney disease, concomitant therapy), as well as the relevance of timely diagnosis and treatment of this condition.